2017
DOI: 10.1186/s11671-017-2009-9
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Graphene with Chemical Modification as Transparent Conducting Electrodes in Organic Light-Emitting Diode

Abstract: Graphene is a promising candidate for the replacement of the typical transparent electrode indium tin oxide in optoelectronic devices. Currently, the application of polycrystalline graphene films grown by chemical vapor deposition is limited for their low electrical conductivity due to the poor transfer technique. In this work, we developed a new method of preparing tri-layer graphene films with chemical modification and explored the influence of doping and patterning process on the performance of the graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…AuCl 3 has been also used as dopants for the modification of trilayer graphene films, which shows a decreased sheet resistance of 150 Ω sq −1 with transmittance above 91% in the visible region. Moreover, doping with AuCl 3 increases the performance of OLEDs based on the doped films because of the contribution of doping to the conductivity …”
Section: Graphene‐based Hybrid Materialsmentioning
confidence: 99%
“…AuCl 3 has been also used as dopants for the modification of trilayer graphene films, which shows a decreased sheet resistance of 150 Ω sq −1 with transmittance above 91% in the visible region. Moreover, doping with AuCl 3 increases the performance of OLEDs based on the doped films because of the contribution of doping to the conductivity …”
Section: Graphene‐based Hybrid Materialsmentioning
confidence: 99%
“…There are several methods to increase the electrical conductivity of CVD graphene such as doping, combining with metal nanowires and creating complex multilayer graphene-based structures. 1,2 It was demonstrated that in the doped CVD graphene the sheet resistance could be lowered down to 100 =W. 2 At the same time, a reasonable sheet resistance is considered to be $ 50 =W.…”
Section: Introductionmentioning
confidence: 99%
“…Several deposition techniques, such as chemical vapor deposition (CVD) [15], ink-jet printing [16] or spin-coating [17], may be employed to grow the OLED devices, which have a basic structure consisting, from bottom to top, of transparent substrate and electrode, a hole injection layer, a polymer active layer and a cathode. In this paper, poly(3,4-ethylenedioxythiphene):poly (styrenesulfonate) (PEDOT:PSS) has been used as hole injection layer, and a hybrid organic-inorganic nanocomposite, composed by a blend of cadmium sulfide (CdS) nanoparticles in a matrix of poly( N -vinylcarbazole) (PVK), as active layer.…”
Section: Introductionmentioning
confidence: 99%